Impact of SiO2 Modification on the Performance of Nafion Composite Membrane - Shuangjie Liu; Jialin Yu; Yongping Hao; Feng Gao; Mo Zhou; Lijun Zhao (International Journal of Polymer Science)
Using Nafion212 membrane and TEOS solution as raw materials, Nafion212/SiO2 composite membranes were prepared. In the in situ sol-gel reaction process, a series of Nafion/SiO2 composite membranes were prepared by varying the reaction temperature and reaction time. The effects of different modification schemes on Nafion/SiO2 composite membranes were studied using SEM, EDS, TEM, TGA, XRD, and mechanical tensile experiments, among other methods. The results show that Nafion/SiO2 composite membranes prepared at 3°C exhibit a well-separated phase structure and excellent water retention properties, with a water uptake of 29.23% and a swelling ratio of 24.25%. These membranes also demonstrate outstanding physical and chemical performance, with a maximum tensile stress of 13.6 MPa and an elongation at a break of 270%. At 110°C, the proton conductivity of the Nafion/SiO2 composite membrane reaches 0.172 S/cm, meeting the requirements for high-temperature proton exchange membrane fuel cells.